A supported catalyst and preparation method thereof

By combining bis(1-methylimidazolyl)ethane and 1,10-phenanthroline with nickel salt and using caffeine to prepare alumina-silica composite support, the problem of insufficient double bond selectivity and activation performance of existing catalysts is solved, and more efficient hydrogenation catalytic effect and optimization of the porous structure of the support is achieved.

CN119237021BActive Publication Date: 2025-02-28LINQU HENGHUI NEW MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411764902.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-02-28
Estimated Expiration
2044-12-04

AI Technical Summary

Technical Problem

The selectivity and activation performance of existing catalysts for double bonds during hydrogenation process are insufficient, resulting in excessive by-products, affecting product quality, and the porous structure of the support is difficult to control, affecting the performance of the catalyst.

Method used

The selectivity and activity of the catalyst are enhanced by combining the nickel salt with tert-butyl modified bis(1-methylimidazolyl)ethane and 1,10-phenanthroline as bisligands to form a bisligand nickel complex, and caffeine is used as a template agent.

Benefits of technology

It significantly improves the selectivity and activation ability of the catalyst to double bonds, reduces the generation of by-products, extends the service life of the catalyst, and improves the porous structure and adsorption ability of the support.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119237021B_ABST
    Figure CN119237021B_ABST
Patent Text Reader

Abstract

The present invention provides a kind of loaded catalyst and preparation method thereof, belong to the technical field of hydrogenation catalyst, comprise the following steps: prepare double ligand nickel complex solution, dissolve tert-butyl modified bis (1 methylimidazolyl) ethane and 1,10 phenanthroline in anhydrous ethanol, stir, add nickel salt, stir evenly again, obtain double ligand nickel complex solution; prepare aluminum oxide silicon oxide composite support, add caffeine solution and alkali solution to the mixed solution of aluminum precursor solution and silicon precursor solution, stir evenly, gelate, obtain aluminum oxide silicon oxide composite support after two-step calcination, immerse the aluminum oxide silicon oxide composite support in double ligand nickel complex solution, stir evenly, filter, wash and dry, obtain loaded catalyst. The technical scheme provided by the present invention realizes the purpose of efficient hydrogenation of loaded catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of hydrogenation catalysts, and in particular to a supported catalyst and a preparation method thereof. Background Art

[0002] In order to improve the performance of polymers containing unsaturated bonds, selective hydrogenation is usually used to improve their temperature resistance, weather resistance, oxygen resistance, heat resistance, aging resistance and tensile properties. Through this process, the unsaturated bonds in the polymer can be hydrogenated into saturated structures. After hydrogenation, the degree of hydrogenation of the unsaturated bonds of olefins reaches more than 98%, while the degree of hydrogenation of the benzene ring is controlled below 5%. This selective hydrogenation not only significantly changes the physical and chemical properties of the polymer, but also effectively expands its application areas. Through this method, the application potential of polymers in industries such as automobiles, construction, electronics and medicine is further enhanced, showing better durability and stability.

[0003] The catalysts currently used do not have sufficient selectivity and activation performance for double bonds during the catalytic process, resulting in a large number of by-products in the product, affecting the product quality. Although some heterogeneous catalysts have good industrial application prospects, their recovery and reuse performance needs to be further optimized to ensure that they can maintain stable hydrogenation activity and selectivity after multiple uses.

[0004] It is difficult to control the formation of a porous structure of alumina-silicon oxide composite catalyst carriers prepared by prior art, and the porosity is low, which makes it difficult to uniformly load the active components, thus affecting the performance of the overall catalyst.

[0005] Therefore, it is necessary to provide a supported catalyst and a preparation method thereof to solve the problems existing in the above-mentioned prior art. Summary of the invention

[0006] In view of this, the present invention provides a supported catalyst and a preparation method thereof, by using tert-butyl-modified bis(1-methylimidazolyl)ethane and 1,10-phenanthroline dual ligands to improve the double bond selectivity and activity of the catalyst, and then using caffeine as a template to prepare an alumina-silica carrier to achieve a porous effect of the catalyst carrier, thereby enhancing the adsorption capacity and catalytic activity.

[0007] The specific scheme of the present invention is as follows: a method for preparing a supported catalyst comprises the following steps:

[0008] Step S1, preparing a dual-ligand nickel complex solution, dissolving tert-butyl-modified bis(1-methylimidazolyl)ethane and 1,10-phenanthroline in anhydrous ethanol, stirring, adding nickel salt, and stirring again to obtain a dual-ligand nickel complex solution;

[0009] Step S2, preparing an alumina-silicon oxide composite carrier, adding a caffeine solution and an alkali solution to a mixed solution of an aluminum precursor solution and a silicon precursor solution, stirring evenly, performing gelation, and obtaining an alumina-silicon oxide composite carrier after two-step calcination;

[0010] Step S3, immersing the alumina-silicon oxide composite support into the dual ligand nickel complex solution, stirring evenly, filtering, washing and drying to obtain a supported catalyst.

[0011] This scheme uses a double ligand nickel-supported catalyst, which effectively improves the activity and selectivity of the supported catalyst for polymer double bonds. Bis(1-methylimidazolyl)ethane as a bidentate nitrogen ligand can form a stable complex with nickel ions, and its bidentate coordination can provide a better electronic environment for nickel, significantly enhancing the affinity of nickel for double bonds. This enhancement can effectively improve the selectivity of the catalyst for double bonds, thereby increasing the degree of hydrogenation of double bonds, while reducing the hydrogenation of unsaturated structures such as benzene rings, effectively reducing the generation of by-products, and can stabilize the nickel active center through the multi-point coordination provided by the ligand to prevent it from agglomerating or deactivating during the reaction, thereby extending the service life of the catalyst. The imidazole group in bis(1-methylimidazolyl)ethane acts as an electron-donating ligand, which can promote the activation of nickel for double bonds by increasing the electron density of nickel, and preferentially hydrogenates double bonds, thereby reducing side reactions. The bidentate structure can form a moderate steric hindrance around the nickel center. This steric hindrance effect can prevent larger molecules or non-target reactants from approaching the nickel active center, further improving the selectivity of the catalyst for double bonds.

[0012] Bis(1-methylimidazolyl)ethane can improve the selectivity for double bonds, but its steric hindrance effect is limited and cannot completely avoid hydrogenation of benzene rings or other unsaturated structures. Therefore, tert-butyl is used to modify bis(1-methylimidazolyl)ethane. The tert-butyl group is a large alkyl group that forms a physical barrier on the catalyst surface, which can significantly increase the steric hindrance of the catalyst surface, effectively preventing non-target reactants from approaching the nickel active center, and facilitating the smaller and more suitable double bonds to approach the nickel active center, thereby enhancing the catalyst's selectivity for hydrogenation of double bonds.

[0013] In order to further increase the catalyst's ability to activate double bonds, 1,10-phenanthroline was compounded on the basis of tert-butyl-modified bis(1-methylimidazolyl)ethane to form a dual ligand. 1,10-phenanthroline can provide additional electron density for the nickel center, further increasing the electron density of the metal nickel active site, making it have a higher activation ability for double bonds. The conjugated system of phenanthroline enhances the catalytic performance of nickel through π-metal interaction, improves the selectivity of the catalyst, and can effectively prevent the occurrence of side reactions. In addition, nickel achieves a more stable complex structure through multiple coordination sites, reduces metal agglomeration and deactivation problems, improves the reusability of the catalyst, and extends the service life of the catalyst. At the same time, the dual ligand nickel-supported catalyst is simple to synthesize, low-cost, and does not require complex post-treatment, reducing production costs.

[0014] Caffeine can spontaneously form nanoscale layered structures or network aggregates through intermolecular hydrogen bonds, π-π stacking and hydrophobic interactions, acting as a template. The molecular stacking of caffeine forms a nanoscale structure, which decomposes and releases gas during subsequent calcination, forming multi-level pores in the material, promoting the formation of microporous and mesoporous structures inside the material, giving the material porosity, and the formed pores are uniform and not easy to collapse during the calcination process.

[0015] Caffeine contains amino groups and nitrogen heterocycles, which can release weak alkaline substances in aqueous solution, adjust the pH, and make silicate and aluminum ions hydrolyze and condense to form a gel structure. Nitrogen-containing groups can increase the alkaline active sites on the surface of the material, thereby enhancing the adsorption capacity of the material surface for gas molecules or liquid compounds.

[0016] Optionally, in step S1, tert-butyl-modified bis(1-methylimidazolyl)ethane is prepared by the following steps: adding bis(1-methylimidazolyl)ethane and tert-butyl bromide to acetonitrile, adding potassium carbonate, heating and stirring, and purifying by silica gel column chromatography to obtain tert-butyl-modified bis(1-methylimidazolyl)ethane.

[0017] Optionally, the bis(1-methylimidazolyl)ethane, tert-butyl bromide and potassium carbonate are all in an anhydrous state; the heating and stirring speed is 400-600 r / min, and the time is 3-4 h.

[0018] Tert-butyl bromide will hydrolyze in the presence of water to produce tert-butyl alcohol and hydrobromic acid, which will not only consume the reactants, but also produce by-products and reduce the yield. Potassium carbonate will also decompose to produce potassium hydroxide in the presence of water, which may cause the pH value of the reaction system to change, affecting the balance and efficiency of the reaction. The anhydrous state can increase the concentration of the reactants, thereby increasing the reaction rate and facilitating the substitution reaction.

[0019] Optionally, in step S1, the nickel salt includes one of nickel sulfate, nickel nitrate and nickel chloride; the stirring speed is 400-500 r / min, and the time is 20-30 min; the stirring speed is again 400-500 r / min, and the time is 50-60 min.

[0020] Optionally, in step S2, the aluminum precursor solution includes one of aluminum nitrate solution, aluminum chloride solution and triethylaluminum solution; the silicon precursor solution includes one of water glass solution, tetraethoxysilane solution and ethyl orthosilicate solution.

[0021] Optionally, in step S2, the two-step calcination process is: the first step of calcination is heating from room temperature to 300°C, the heating rate is 3-4°C / min, and maintaining for 60-70min; the second step of calcination is heating to 400°C, the heating rate is 5-6°C / min, and maintaining for 120-140min.

[0022] The first step is calcination, which is heated from room temperature to 300°C. Caffeine begins to decompose but does not burn, decomposing caffeine into small molecules such as CO 2 , H 2 O, etc. are released, which promotes the formation of pores in the carrier. During low-temperature calcination, the alumina and silica networks are not completely sintered, which helps to slowly release the gas generated by the decomposition of the template, avoiding the rapid release of gas, which may lead to the collapse of the pores or the breakage of the material.

[0023] The second step of calcination is heated from 300℃ to 400℃, which can completely remove the caffeine template, ensure that there is no organic matter left on the surface and in the pores of the material, and provide a pure environment. At high temperatures, the agglomeration between alumina and silica particles is enhanced, and some sintering occurs. This sintering process does not destroy the pore structure, but can make the structure of the carrier more solid, thus giving the carrier excellent stability.

[0024] Through two-step calcination, the template agent caffeine gradually decomposes at low temperature, and the released gas is slowly discharged to avoid a large amount of gas release at one time, which may cause the pores to collapse or the material to break. In the low-temperature stage, the pore structure is initially formed, and in the high-temperature stage, the residual organic matter is thoroughly decomposed to ensure that the pores are more stable and uniform. In addition, the sintering of the material at high temperature fixes the pore structure and enhances the stability of the overall structure.

[0025] Optionally, in step S2, the alkali solution includes one of aqueous ammonia, ammonium bicarbonate, sodium hydroxide and potassium hydroxide solution.

[0026] Optionally, in step S3, the stirring speed is 300-400 r / min and the time is 2.5-3.5 h.

[0027] To achieve the above object, the present invention also provides a supported catalyst prepared by the above method for preparing a supported catalyst.

[0028] Optionally, the following components are included in parts by weight:

[0029] 7-8 parts of nickel salt, 20-30 parts of bis(1-methylimidazolyl)ethane, 5-15 parts of tert-butyl bromide, 1-2 parts of 1,10-phenanthroline, and 10-15 parts of alumina-silicon oxide composite carrier;

[0030] The raw materials of the aluminum oxide-silicon oxide composite carrier include: 20-30 parts of aluminum precursor solution, 20-30 parts of silicon precursor solution, 2-7 parts of alkali solution and 5-10 parts of caffeine.

[0031] The above technical solution of the present invention includes at least the following beneficial effects:

[0032] (1) The present invention introduces tert-butyl-modified bis(1-methylimidazolyl)ethane, and uses the alkyl group of the tert-butyl group to form a physical barrier on the catalyst surface, thereby increasing the steric hindrance on the catalyst surface, which is conducive to the proximity of smaller and more suitable double bonds to the nickel active center, thereby enhancing the catalyst's hydrogenation selectivity for double bonds. The bidentate coordination of bis(1-methylimidazolyl)ethane can provide a better electronic environment for nickel, significantly enhancing nickel's affinity for double bonds, and effectively improving the catalyst's selectivity for double bonds.

[0033] (2) 1,10-phenanthroline and tert-butyl-modified bis(1-methylimidazolyl)ethane were introduced to form a dual ligand. 1,10-phenanthroline can provide additional electron density for the nickel center, further increasing the electron density of the metal nickel active site, making it more capable of activating double bonds. The conjugated system of phenanthroline enhances the catalytic performance of nickel through π-metal interaction, improves the selectivity of the catalyst, and can effectively prevent the occurrence of side reactions.

[0034] (3) The present invention introduces caffeine as a template in the preparation of the alumina-silicon oxide composite porous carrier. Caffeine can spontaneously form a nano-scale layered structure or network aggregate through intermolecular hydrogen bonding, π-π stacking and hydrophobic interaction, acting as a template. During the calcination process, it decomposes and releases gas to promote the carrier to form a porous structure. The amino group and nitrogen heterocycle contained in it can adjust the pH of the solution to promote the gelation process. At the same time, it can also enhance the adsorption capacity of the carrier and promote the catalytic reaction. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is a scanning electron microscope image of the supported catalyst prepared in Example 1 of the present invention;

[0036] Figure 2This is a scanning electron microscope image of the supported catalyst prepared in Example 3 of the present invention. DETAILED DESCRIPTION

[0037] In order to make the purpose, technical solution and advantages of the embodiment of the present invention clearer, the technical solution of the embodiment of the present invention will be clearly and completely described in combination with the embodiment of the present invention. Obviously, the described embodiment is a part of the embodiment of the present invention, not all the embodiments. Based on the described embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present invention.

[0038] Example 1

[0039] 20 parts of bis(1-methylimidazolyl)ethane and 10 parts of tert-butyl bromide were added to 200 parts of acetonitrile, potassium carbonate was added, heated to 60°C, stirred at 500 r / min for 3 hours, and purified by silica gel column chromatography to obtain tert-butyl-modified bis(1-methylimidazolyl)ethane. 8 parts of tert-butyl-modified bis(1-methylimidazolyl)ethane and 2 parts of 1,10-phenanthroline were dissolved in 100 parts of ethanol, stirred at 500 r / min for 20 minutes, and then 8 parts of nickel nitrate were added, and stirred again at 500 r / min for 60 minutes to obtain a dual-ligand nickel complex solution.

[0040] Add 25 parts of aluminum nitrate solution and 25 parts of water glass solution to a beaker and mix well, then slowly add 10 parts of caffeine solution and 2 parts of ammonia solution, stir at 500r / min for 2h, let stand for 24h, and fully gel. Place the gel in a 70℃ oven to dry for 12h, then put it in a muffle furnace and perform two-step calcination, i.e., the first step of calcination is to heat from room temperature to 300℃ at a heating rate of 4℃ / min and keep for 60min; the second step of calcination is to heat from 300℃ to 400℃ at a heating rate of 5℃ / min and keep for 130min to obtain an alumina-silicon oxide composite carrier.

[0041] Under normal pressure and reaction temperature of 60°C, 10 parts of alumina-silicon oxide composite carrier were added to 6 parts of dual ligand nickel complex solution, stirred at 300 r / min for 3 hours to ensure uniform loading, filtered, washed and dried to obtain a supported catalyst.

[0042] Example 2

[0043] 25 parts of bis(1-methylimidazolyl)ethane and 15 parts of tert-butyl bromide were added to 250 parts of acetonitrile, potassium carbonate was added, heated to 60°C, stirred at 400 r / min for 4 hours, and purified by silica gel column chromatography to obtain tert-butyl-modified bis(1-methylimidazolyl)ethane. 8 parts of tert-butyl-modified bis(1-methylimidazolyl)ethane and 2 parts of 1,10-phenanthroline were dissolved in 100 parts of ethanol, stirred at 400 r / min for 25 minutes, and then 7 parts of nickel nitrate were added, and stirred again at 500 r / min for 50 minutes to obtain a dual-ligand nickel complex solution.

[0044] Add 25 parts of aluminum chloride solution and 25 parts of tetraoxyethylsilane solution to a beaker and mix evenly, then slowly add 6 parts of caffeine solution and 5 parts of sodium hydroxide solution, stir at 400r / min for 3h, let stand for 24h, and fully gel. Place the gel in a 60℃ oven to dry for 14h, then put it in a muffle furnace and perform two-step calcination, i.e., the first step of calcination is to heat from room temperature to 300℃ at a heating rate of 3℃ / min and keep for 70min; the second step of calcination is to heat from 300℃ to 400℃ at a heating rate of 6℃ / min and keep for 120min to obtain an alumina-silicon oxide composite carrier.

[0045] Under normal pressure and reaction temperature of 60°C, 12 parts of alumina-silicon oxide composite carrier were added to 7 parts of dual ligand nickel complex solution, stirred at 350 r / min for 3 hours to ensure uniform loading, filtered, washed and dried to obtain a supported catalyst.

[0046] Example 3

[0047] 30 parts of bis(1-methylimidazolyl)ethane and 5 parts of tert-butyl bromide were added to 350 parts of acetonitrile, potassium carbonate was added, heated to 60°C, stirred at 500 r / min for 3.5 hours, and purified by silica gel column chromatography to obtain tert-butyl-modified bis(1-methylimidazolyl)ethane. 8 parts of tert-butyl-modified bis(1-methylimidazolyl)ethane and 1 part of 1,10-phenanthroline were dissolved in 100 parts of ethanol, stirred at 450 r / min for 30 minutes, and then 7 parts of nickel nitrate were added, and stirred again at 400 r / min for 55 minutes to obtain a double ligand nickel complex solution.

[0048] Add 30 parts of aluminum nitrate solution and 25 parts of tetraoxyethylsilane solution to a beaker and mix well, then slowly add 8 parts of caffeine solution and 4 parts of potassium hydroxide solution, stir at 450r / min for 2h, let stand for 24h, and fully gel. Place the gel in an oven at 80°C and dry for 10h, then place it in a muffle furnace and perform two-step calcination, i.e., the first step of calcination is to heat from room temperature to 300°C at a heating rate of 4°C / min and keep for 60min; the second step of calcination is to heat from 300°C to 400°C at a heating rate of 5°C / min and keep for 140min to obtain an alumina-silicon oxide composite carrier.

[0049] Under normal pressure and reaction temperature of 60°C, 13 parts of alumina-silicon oxide composite carrier were added to 5 parts of dual ligand nickel complex solution, stirred at 300 r / min for 3.5 h to ensure uniform loading, filtered, washed and dried to obtain a supported catalyst.

[0050] Example 4

[0051] 20 parts of bis(1-methylimidazolyl)ethane and 15 parts of tert-butyl bromide were added to 200 parts of acetonitrile, potassium carbonate was added, heated to 60°C, stirred at 600 r / min for 3 hours, and purified by silica gel column chromatography to obtain tert-butyl-modified bis(1-methylimidazolyl)ethane. 8 parts of tert-butyl-modified bis(1-methylimidazolyl)ethane and 1.5 parts of 1,10-phenanthroline were dissolved in 100 parts of ethanol, stirred at 430 r / min for 25 minutes, and then 7 parts of nickel nitrate were added, and stirred again at 480 r / min for 50 minutes to obtain a dual-ligand nickel complex solution.

[0052] Add 25 parts of aluminum chloride solution and 30 parts of ethyl orthosilicate solution to a beaker and mix evenly, then slowly add 5 parts of caffeine solution and 7 parts of ammonium bicarbonate solution, stir at 400r / min for 2.5h, let stand for 24h, and fully gel. Place the gel in a 75℃ oven to dry for 11h, then put it in a muffle furnace and perform two-step calcination. The first step of calcination is to heat from room temperature to 300℃ at a heating rate of 4℃ / min and keep for 70min; the second step of calcination is to heat from 300℃ to 400℃ at a heating rate of 6℃ / min and keep for 120min to obtain an alumina-silicon oxide composite carrier.

[0053] Under normal pressure and reaction temperature of 60°C, 15 parts of alumina-silicon oxide composite carrier were added to 7 parts of dual ligand nickel complex solution, stirred at 350 r / min for 2.5 h to ensure uniform loading, filtered, washed and dried to obtain a supported catalyst.

[0054] Example 5

[0055] 30 parts of bis(1-methylimidazolyl)ethane and 10 parts of tert-butyl bromide were added to 300 parts of acetonitrile, potassium carbonate was added, heated to 60°C, stirred at 500 r / min for 4 hours, and purified by silica gel column chromatography to obtain tert-butyl-modified bis(1-methylimidazolyl)ethane. 8 parts of tert-butyl-modified bis(1-methylimidazolyl)ethane and 2 parts of 1,10-phenanthroline were dissolved in 100 parts of ethanol, stirred at 470 r / min for 20 minutes, and then 7 parts of nickel nitrate were added, and stirred again at 420 r / min for 55 minutes to obtain a dual-ligand nickel complex solution.

[0056] Add 30 parts of triethylaluminum solution and 20 parts of ethyl orthosilicate solution to a beaker and mix evenly, then slowly add 9 parts of caffeine solution and 3 parts of ammonia solution, stir at 500r / min for 2.5h, let stand for 24h, and fully gel. Place the gel in an oven at 65°C and dry for 13h, then put it in a muffle furnace and perform two-step calcination, i.e., the first step of calcination is to heat from room temperature to 300°C at a heating rate of 4°C / min and keep for 60min; the second step of calcination is to heat from 300°C to 400°C at a heating rate of 6°C / min and keep for 130min to obtain an alumina-silicon oxide composite carrier.

[0057] Under normal pressure and reaction temperature of 60°C, 10 parts of alumina-silicon oxide composite carrier were added to 6 parts of dual ligand nickel complex solution, stirred at 400 r / min for 2.5 h to ensure uniform loading, filtered, washed and dried to obtain a supported catalyst.

[0058] Example 6

[0059] 20 parts of bis(1-methylimidazolyl)ethane and 10 parts of tert-butyl bromide were added to 200 parts of acetonitrile, potassium carbonate was added, heated to 60°C, stirred at 450 r / min for 3 hours, and purified by silica gel column chromatography to obtain tert-butyl-modified bis(1-methylimidazolyl)ethane. 8 parts of tert-butyl-modified bis(1-methylimidazolyl)ethane and 1 part of 1,10-phenanthroline were dissolved in 100 parts of ethanol, stirred at 400 r / min for 30 minutes, and then 7 parts of nickel nitrate were added, and stirred again at 400 r / min for 60 minutes to obtain a dual-ligand nickel complex solution.

[0060] Add 20 parts of triethylaluminum solution and 30 parts of water glass solution to a beaker and mix evenly, then slowly add 7 parts of caffeine solution and 5 parts of ammonium bicarbonate solution, stir at 500r / min for 2h, let stand for 24h, and fully gel. Place the gel in an oven at 60-80℃ and dry for 12h, then put it in a muffle furnace and perform two-step calcination. The first step of calcination is to heat from room temperature to 300℃ at a heating rate of 3℃ / min and keep for 70min; the second step of calcination is to heat from 300℃ to 400℃ at a heating rate of 5℃ / min and keep for 130min to obtain an alumina-silicon oxide composite carrier.

[0061] Under normal pressure and reaction temperature of 60°C, 11 parts of alumina-silicon oxide composite carriers were added to 5 parts of dual ligand nickel complex solution, stirred at 300 r / min for 3.5 hours to ensure uniform loading, filtered, washed and dried to obtain a supported catalyst.

[0062] The present invention also carried out comparative examples and related tests

[0063] Comparative Example 1

[0064] The difference between Comparative Example 1 and Example 1 is that the dual-ligand nickel complex is not used, but nickel salt is used instead of the dual-ligand nickel complex. The other compositions and preparation methods are the same as those of Example 1, and a supported catalyst is prepared.

[0065] Comparative Example 2

[0066] The difference between Comparative Example 2 and Example 1 is that caffeine is not used in the preparation of the alumina-silicon oxide composite carrier, and other compositions and preparation methods are the same as those of Example 1, to prepare a supported catalyst.

[0067] Comparative Example 3

[0068] The difference between Comparative Example 3 and Example 1 is that tert-butyl group is not used to modify bis(1-methylimidazolyl)ethane. Instead, bis(1-methylimidazolyl)ethane and 1,10-phenanthroline are used to prepare the dual ligand. The other compositions and preparation methods are the same as those in Example 1, and a supported catalyst is prepared.

[0069] Comparative Example 4

[0070] The difference between Comparative Example 4 and Example 1 is that only 1,10-phenanthroline single ligand is used, and other compositions and preparation methods are the same as those of Example 1, to prepare a supported catalyst.

[0071] Performance testing

[0072] The catalyst parameters prepared in Examples 1-6 and Comparative Examples 1-4 are shown in Table 1 below.

[0073] Table 1

[0074]

[0075] From the data in Table 2, it can be seen that the catalysts prepared in Examples 1-6 of the present invention and Comparative Examples 1 and 3-4 all have good specific surface area and pore volume, which are conducive to the catalytic reaction. The specific surface area and pore volume of the catalyst prepared in Comparative Example 2 are significantly reduced, indicating that caffeine is conducive to the preparation of the catalyst carrier and promotes the formation of a porous structure. The catalysts prepared in Examples 1 and 3 were scanned by electron microscope, and the results are as follows: Figure 1 and Figure 2 shown.

[0076] The catalysts prepared in the above Examples 1-6 and Comparative Examples 1-4 were respectively used for catalytic hydrogenation reaction tests. The tests were all maintained under the same reaction conditions: reaction pressure of 7.0 MPa, reaction temperature of 170°C, 1000 mL SBS (styrene-butadiene-styrene block copolymer) concentration of 5 wt%, reaction time of 4 hours. After the reaction, the products obtained from the above hydrogenation tests were tested and the data were summarized. The results are shown in Table 2 below.

[0077] Table 2

[0078]

[0079] Note: In Table 2, St is a benzene ring group; Bd 1,2 Butene 1,2-yl; Bd 1,4 1,4-butene; the raw material is from the rubber plant of Beijing Yanshan Branch of Sinopec; the total degree of hydrogenation = (St+Bd 1,2 +Bd 1,4 )% / 3.

[0080] It can be seen from the result data in Table 2 that the supported catalysts obtained in Examples 1-6 of the present invention have good hydrogenation selectivity for double bonds.

[0081] According to the comparison between Comparative Example 1 and Examples 1-6, the use of nickel salts to replace the double ligand nickel complex results in St, Bd 1,2 and Bd 1,4The hydrogenation degrees of the catalysts prepared in Comparative Example 2 all decreased to a large extent, and the total hydrogenation degree decreased significantly, indicating that the dual-ligand nickel complex effectively improved the catalytic performance of nickel and improved the selectivity of the catalyst for double bonds; as can be seen from the comparison between Comparative Example 2 and Examples 1-6, the hydrogenation degrees of each component in the hydrogenation test of the catalyst prepared in Comparative Example 2 decreased, indicating that the porous structure of the catalyst carrier deteriorated and the adsorption capacity decreased, resulting in reduced catalytic performance; as can be seen from the comparison between Comparative Example 3 and Examples 1-6, the total hydrogenation degree in the hydrogenation test of the catalyst prepared in Comparative Example 3 decreased, indicating that the tert-butyl group can prevent non-target reactants from approaching the nickel active center, effectively improving the selectivity of the catalyst for double bonds; as can be seen from Comparative Example 4 and Examples 1-6, using only 1,10-phenanthroline single ligand will reduce the hydrogenation degree, indicating that the single ligand is insufficient to improve the double bond selectivity of the nickel catalyst.

[0082] The above are preferred embodiments of the present invention. It should be pointed out that, for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.

Claims

1. A method for preparing a supported catalyst, characterized in that: The following steps are involved: Step S1, preparing a dual-ligand nickel complex solution, dissolving tert-butyl-modified bis(1-methylimidazolyl)ethane and 1,10-phenanthroline in anhydrous ethanol, stirring, adding nickel salt, and stirring again to obtain a dual-ligand nickel complex solution; Step S2, preparing an alumina-silicon oxide composite carrier, adding a caffeine solution and an alkali solution to a mixed solution of an aluminum precursor solution and a silicon precursor solution, stirring evenly, performing gelation, and obtaining an alumina-silicon oxide composite carrier after two-step calcination; Step S3, immersing the alumina-silicon oxide composite support into the dual ligand nickel complex solution, stirring evenly, filtering, washing and drying to obtain a supported catalyst.

2. The method for preparing a supported catalyst according to claim 1, characterized in that: In step S1, tert-butyl-modified bis(1-methylimidazolyl)ethane is prepared by the following steps: adding bis(1-methylimidazolyl)ethane and tert-butyl bromide to acetonitrile, adding potassium carbonate, heating and stirring, and purifying by silica gel column chromatography to obtain tert-butyl-modified bis(1-methylimidazolyl)ethane.

3. The method for preparing a supported catalyst according to claim 2, characterized in that: The bis(1-methylimidazolyl)ethane, tert-butyl bromide and potassium carbonate are all in anhydrous state; the heating and stirring speed is 400-600 r / min, and the time is 3-4 h.

4. The method for preparing a supported catalyst according to claim 1, characterized in that: In the step S1, the nickel salt includes one of nickel sulfate, nickel nitrate and nickel chloride; the stirring speed is 400-500 r / min for 20-30 min; and the stirring speed is again 400-500 r / min for 50-60 min.

5. The method for preparing a supported catalyst according to claim 1, characterized in that: In the step S2, the aluminum precursor solution includes one of aluminum nitrate solution, aluminum chloride solution and triethylaluminum solution; the silicon precursor solution includes one of water glass solution, tetraethoxysilane solution and ethyl orthosilicate solution.

6. The method for preparing a supported catalyst according to claim 1, characterized in that: In step S2, the two-step calcination process is as follows: the first step of calcination is heating from room temperature to 300°C at a heating rate of 3-4°C / min and maintaining for 60-70min; the second step of calcination is heating to 400°C at a heating rate of 5-6°C / min and maintaining for 120-140min.

7. The method for preparing a supported catalyst according to claim 1, characterized in that: In step S2, the alkali solution includes one of aqueous ammonia, ammonium bicarbonate, sodium hydroxide and potassium hydroxide solution.

8. The method for preparing a supported catalyst according to claim 1, characterized in that: In step S3, the stirring speed is 300-400 r / min and the time is 2.5-3.5 h.

9. A supported catalyst, characterized in that The catalyst is prepared by the method for preparing a supported catalyst according to any one of claims 1 to 8.

10. A supported catalyst according to claim 9, characterized in that: The composition comprises the following components in parts by weight: 7-8 parts of nickel salt, 20-30 parts of bis(1-methylimidazolyl)ethane, 5-15 parts of tert-butyl bromide, 1-2 parts of 1,10-phenanthroline, and 10-15 parts of alumina-silicon oxide composite carrier; The raw materials of the aluminum oxide-silicon oxide composite carrier include: 20-30 parts of aluminum precursor solution, 20-30 parts of silicon precursor solution, 2-7 parts of alkali solution and 5-10 parts of caffeine.

Citation Information

Patent Citations

  • Ethylene oligomerization catalyst, preparation method and usage thereof

    CN101781231A

  • Microporous zinc (II) coordination polymer crystal and preparation method and application thereof

    CN108623816A